Fuel consumption and emission prediction by Iranian power plants until 2025 - Mazandarani, A.; Mahlia, T.M.I.; Chong, W.T.; Moghavvemi, Mahmoud (Elsevier, 2011)
Electricity consumption has grown eleven-times within the last 30 years in Iran, which has resulted in about 118 Mtons in CO2 emission in 2009. Economic growth in Iran depends on electricity; therefore, the trend of electricity generation should keep going in the future to guarantee this growth. In view of this need, the country has to build many new power plants. If most of them are thermal types, the CO2 and other air pollutant emissions will increase and cause harmful environmental effects. In this paper, Iranian future power plant composition is investigated to predict the fuel consumption and emissions until 2025, which is the end of the country's 20-year vision plan (2006-2025). Government is planning to change the structure of power industries to a more variety and fewer shares of fossil fuel bases. The results showed that in this new composition, consumption of natural gas will increase by 47% and diesel by 50% by 2025. Coal consumption in power plants will reach to 10,826 ktons in the same time span. Whereas if the old composition continues in the future, fuel consumption will increase by 130%, 106% and 69% for natural gas, diesel and fuel oil respectively. It is also found that by 2025, CO2 emission will increase another 2.1 times for the old and 1.6 times for the new power plant composition which government is planning to do.